Multisynchronization of Chaotic Oscillators via Nonlinear Observer Approach - Ricardo Aguilar-López; Rafael Martínez-Guerra; Juan L. Mata-Machuca (The Scientific World Journal)
The goal of this work is to synchronize a class of chaotic oscillators in a master-slave scheme, under different initial conditions, considering several slaves systems. The Chen oscillator is employed as a benchmark model and a nonlinear observer is proposed to reach synchronicity between the master and the slaves’ oscillators. The proposed observer contains a proportional and integral form of a bounded function of the synchronization error in order to provide asymptotic synchronization with a satisfactory performance. Numerical experiments were carried out to show the operation of the considered methodology.